Surface functionalization of polypropylene and polyethylene films with allylamine by γ radiation. (16th November 2018) - Pérez-Calixto, M.; González-Pérez, G.; Dionisio, N.; Bucio, E.; Burillo, G.; García-Uriostegui, L.
Abstract: Abstract : Allylamine (AA)-functionalized surfaces for cell adhesion and tissue engineering generated by plasma reactions present several disadvantages, such as amine degradation after 1 week of storage in air and difficulty in achieving a highly specific surface functionalization. In this work, polypropylene (PP) and polyethylene (PE) films were functionalized with AA by γ irradiation to enhance adhesion and compatibility without changing intrinsic bulk properties, thus avoiding the disadvantages of plasma synthesis. Irradiation grafting was realized by a direct and pre-irradiation oxidation method. The effect of different parameters studied were characterized by Fourier transform infrared spectra, thermogravimetric analysis, differential scanning calorimetry, scanning electron microscopy, and contact angle measurements.